Gender-sensitive analysis of resynchronization therapy indications in 2021 European heart failure guidelines. (3rd October 2022) - Rilo, I; Beramendi Calero, J; Quintas Ovejero, L; Rengel Jimenez, A; Cea Primo, D; Nunez Rodriguez, A; Hernandez De Alba, L; Calvo Chumillas, S; Aldave Zabaleta, P; Querejeta Iraola, R
Abstract: Introduction: Although there is evidence that women benefit very much more than men from resynchronization therapies even with narrower QRSs, the clinical practice guidelines for heart failure do not contemplate a different attitude taking into account gender. Objective: The aim of this study is to analyze the clinical trials and registries on which the recommendations of the guidelines are based. Methods: We selected in the bibliography of the 2021 European heart failure guidelines the registries and clinical essays and analyzed them attending to gender perspective according to the following questions: Is gender treated as a primary variable? Is gender treated as a secondary variable? Is there a differentiated analysis by sex? Are side effects described differently by sex? What is the proportion of women in the study? Results: We analyzed 16 articles. The proportion of women is between 15 and 25%. Only 6 in 16 articles reported a differentiated analysis by sex and there was only one article that differentiated side effects according to sex. Conclusions: Gender analysis should be mandatory in all the clinical essays carried out in the future. Guidelines should consider different recommendations according to gender. Being excluded or infrarrepresented in studies could conditionate a discrimination to women not only now but also in the future when the algorithms of artificial intelligence condition the decisions we make in the different pathologies Funding Acknowledgement: Type of funding sources: None.